THE MODERATE EFFECT OF ABSORPTIVE CAPACITY ON THE EFFECT OF RISK TAKING AND WORK ATMOSPHERE ON COMPETENCE ENTREPRENEURS AT PD HORAS JAYA PASAR PEMATANGSIANTAR - tutik susanti; liharman saragih; elfina damanik (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of risk taking and entrepreneurial competencies on entrepreneurial competencies moderated by absorptive capacity. This research was conducted using quantitative methods through interviews, questionnaires and documentation of 48 samples of tailors at PD Pasar Horas Jaya. The data analysis technique used is data instrument test, classical assumption, multiple linear regression analysis, t test, coefficient of determination test, and MRA. The analysis was performed using the IBM SPSS Statistics V.26 program. The results showed that through multiple linear regression risk taking had an effect on entrepreneur competencies with a sig. 0.00 1. Work atmosphere has a positive effect on entrepreneur competencies with a value of sig.0.00. From the results of the MRA test, it is known that absorptive capacity does not affect the relationship between risk taking and entrepreneurial competencies with sig values ??of 0.431 and 0.67, respectively. The results of the second MRA test show that absorptive capacity does not affect the relationship between work atmosphere and entrepreneur competencies with sig values ??of 0.772 and 0.442, respectively.